ANALISIS PROFESIONALISME, KESEJAHTERAAN, DAN PENGEMBANGAN PROFESI GURU SEKOLAH DASAR - Reski Permata Sari; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze teacher professionalism, welfare, and professional development in primary schools. The research was conducted at SD As’Adiyah 4 Baru Impa-Impa using a qualitative descriptive approach. Data were collected through interviews, observations, document analysis, and focus group discussions involving the principal, senior teachers, junior/honorary teachers, and administrative staff. The findings indicate that teacher professionalism has generally been well implemented, as reflected in strong collaboration, positive work ethics, and a supportive school environment. However, teacher welfare, particularly related to salary, certification, and professional allowances, has not been evenly distributed, especially for junior and honorary teachers. Professional development activities such as Teacher Working Groups (KKG) have contributed positively to improving teaching competence, although their implementation is still limited in frequency and participation. Strengthening certification programs, improving welfare policies, and expanding sustainable professional development are essential to enhance teacher motivation and the quality of learning in primary schools.